Quasi-experimental Study: The Effect of Problem Based Learning Model Assisted by Fyrebox on Students Mathematics Learning Outcomes - Rosyadi, Farah Aprilia; Wijayanti, Rica (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Fyrebox on students' mathematics learning outcomes. Methodology: This research employed a quantitative approach with a quasi-experimental Posttest-Only Control Group Design. The subjects consisted of 29 students in the experimental group and 30 students in the control group, all from grade XI of Kamal 1 State High School. The research instrument was a post-test in the form of problem-based essay questions. Data were analyzed using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, and the Mann-Whitney U test with the assistance of SPSS 21. Main Findings: The results showed a significance value of 0.000 < 0.05 in the Mann-Whitney U test, indicating a significant effect of the PBL model assisted by Fyrebox on students' mathematics learning outcomes. The experimental group outperformed the control group in both average score and percentage of completeness. Novelty/Originality of this study: This study offers originality by integrating the Fyrebox game-based quiz platform into the Problem Based Learning model to enhance student engagement and performance in mathematics. Unlike previous studies that implemented PBL alone or used other digital tools, this research highlights the effectiveness of Fyrebox as a gamified medium that contributes to improved learning outcomes in the digital learning era.